2007
DOI: 10.1097/01.wnf.0000240955.49315.65
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Topiramate on Plasma Concentrations of Clozapine, Olanzapine, Risperidone, and Quetiapine in Patients With Psychotic Disorders

Abstract: These findings indicate that topiramate, at the dosages recommended for use as a mood stabilizer, does not affect the plasma levels of the new antipsychotics-clozapine, olanzapine, risperidone, and quetiapine.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 28 publications
1
11
0
Order By: Relevance
“…A randomized, double‐blind, placebo‐controlled trial in patients with treatment‐resistant schizophrenia has shown that the addition of topiramate, 300 mg/day, to an ongoing treatment with newer antipsychotics did not significantly alter plasma concentrations of clozapine and olanzapine in 12 and 5 patients, respectively [144]. A recent study in 38 patients with psychotic disorders has documented that topiramate, at the dosages up to 200 mg/day, does not affect steady‐state plasma levels of the new antipsychotics clozapine, olanzapine, risperidone and quetiapine [145].…”
Section: Metabolic Drug Interactions Of Newer Antipsychoticsmentioning
confidence: 99%
“…A randomized, double‐blind, placebo‐controlled trial in patients with treatment‐resistant schizophrenia has shown that the addition of topiramate, 300 mg/day, to an ongoing treatment with newer antipsychotics did not significantly alter plasma concentrations of clozapine and olanzapine in 12 and 5 patients, respectively [144]. A recent study in 38 patients with psychotic disorders has documented that topiramate, at the dosages up to 200 mg/day, does not affect steady‐state plasma levels of the new antipsychotics clozapine, olanzapine, risperidone and quetiapine [145].…”
Section: Metabolic Drug Interactions Of Newer Antipsychoticsmentioning
confidence: 99%
“…Antidepressants, such as paroxetine (Saito et al 2005), sertraline (Spina et al 2004), and fluoxetine (Bondolfi et al 2002), can increase the concentration of risperidone and its metabolite paliperidone, but this is not the case for valproic acid (Ravindran et al 2004; Yoshimura et al 2007), topirimate (Migliardi et al 2007), lamotrigine (Spina et al 2006), mirtazapine (Loonen et al 1999), and venlafaxine (Amchin et al 1999). Carbamazapine can decrease the concentration of the metabolite paliperidone in patients receiving risperidone (Spina et al 2000).…”
Section: Development Of Paliperidonementioning
confidence: 99%
“…Plasma concentrations of quetiapine were found to be either unchanged or increased in psychiatric patients during coadministration with valproic acid [10][11][12]. There is limited or no information concerning the effect of lamotrigine and other antiepileptic agents that are also occasionally used to treat psychiatric disorders, such as topiramate and oxcarbazepine, on the pharmacokinetics of quetiapine [11,13].…”
Section: Introductionmentioning
confidence: 99%